2018
DOI: 10.1525/elementa.331
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing remote sensing to address critical science questions on ocean-atmosphere interactions

Abstract: Earth observing systems have proven to be a unique source of long-term synoptic information on numerous physical, chemical and biological parameters on a global scale. Merging this information for integrated studies that peruse key questions about the ocean-atmosphere interface is, however, very challenging. Such studies require interdisciplinary frameworks and novel insights into ways to address the problem. We present here a perspective review on how current and emerging remote sensing technologies could hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 315 publications
(367 reference statements)
0
23
0
Order By: Relevance
“…Fortunately, our ability to observe SCMs in remote Arctic marine systems will dramatically improve in the coming years. Although SCMs are invisible to ocean-colour sensors, there is the exciting prospect that new Lidar sensors will be able to detect these features from space [43]. Meanwhile, the increased use of ice-tethered profilers [44], Bio-ARGO floats [45], animal-borne instruments [46] and autonomous underwater vehicles [47,48] will allow us to monitor the seasonal dynamics of SCM vertical structure at an unprecedented spatial resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, our ability to observe SCMs in remote Arctic marine systems will dramatically improve in the coming years. Although SCMs are invisible to ocean-colour sensors, there is the exciting prospect that new Lidar sensors will be able to detect these features from space [43]. Meanwhile, the increased use of ice-tethered profilers [44], Bio-ARGO floats [45], animal-borne instruments [46] and autonomous underwater vehicles [47,48] will allow us to monitor the seasonal dynamics of SCM vertical structure at an unprecedented spatial resolution.…”
Section: Resultsmentioning
confidence: 99%
“…The current model version does not account for increases in sulfuric acid condensation sink due to increased emissions of sea salt and organic aerosols from the open ocean, which may lead to overestimates in nucleation rates in the simulations. However, there is no consensus on the CCN activity of sea spray aerosols (including primary organic aerosols and sea salts; Neukermans et al, 2018). Based on historical shipboard observations, Quinn et al (2017) concluded that a small fraction of marine cloud condensation nuclei are made up of sea spray aerosol especially in regions north of 60 • N. Leaitch et al (2016), based on recent observations in the Arctic region, also found that small particles (up to 20 nm) are activated in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Grandey and Wang (2015) found that artificially enhanced DMS emissions in different latitude bands could potentially offset greenhouse-gas-induced warming across most of the world and especially in the Arctic region. The loss of Arctic sea ice allows further penetration of sunlight into surface ocean water (e.g., Nicolaus et al, 2012) that can increase net production of algae and phytoplankton (e.g., Arrigo and van Dijken, 2015). In addition, when sea ice is melted the surface ocean water is more prone to wind stress (Rainville et al, 2011;Martin et al, 2014) that can enhance air fluxes of DMS and other gases (e.g., Bates et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bean et al, 2017 [27] discussed the impact of RS technologies onmonitoring the whole marine ecosystem models for an integrated and comprehensive approach to impact assessments that can benefit the society in the context of a country, such as the UK. Neukermans et al, 2018 [42] addressed critical science questions on ocean-atmosphere interaction using multiplatform space-borne missions, from visible to microwave, active, and passive sensors. Werdell et al, 2018 [43] have presented state of the art approaches to obtain marine inherent optical properties from ocean colour RS and have defined the areas where existing knowledge gaps remain.…”
Section: Remote Sensing Applications That Could Be Used For Dapsi(w)rmentioning
confidence: 99%